Iter Iaponicum: post-pandemic resumption of the Census of ancient Italian manuscripts and editions preserved in Japan. Early surveys of the vernacular Petrarch - Marco Daniele Limongelli (Bibliothecae.it, 2025)
This essay reports the resumption of the census of early books in Italian language held in Japan, interrupted during the pandemic. Here, the first outcome of the research is anticipated, focusing on the manuscripts and 16th century editions of Petrarch’s works consulted at university libraries. A sample of the information on provenance, circulation, use and owners is offered. The survey also highlights some of the key figures of the Japanese cultural reform who, between the 19th and 20th centuries, opened up to Western culture and contributed significantly to the diffusion of Italian texts in Japan.